2020
DOI: 10.3390/s20092680
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Approach for the Control Measurements of a Ski-Flying Hill Inrun: A Case Study of Planica

Abstract: Ski jumping hills should be prepared for competitions in accordance with project documentation in order to ensure safe and fair conditions for competitors. Geodesy/surveying is essential for guiding preparations and controlling the actual shape of the hill. In this article, we present a methodology for the control measurements and preparation of an inrun for a ski-flying hill in Planica. On each side of the track, there is metal tube that guides the trolley, which mills tracks into the ice. A special platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Urbančič et al [ 48 ] suggested an improved approach for the control measurements of a ski-flying hill run in a case study of Planica. They presented a specially designed platform containing three measuring prisms to control the position of pipes (a metal tube is located on each side of the track to guide the trolley that mills tracks into the ice).…”
Section: Related Workmentioning
confidence: 99%
“…Urbančič et al [ 48 ] suggested an improved approach for the control measurements of a ski-flying hill run in a case study of Planica. They presented a specially designed platform containing three measuring prisms to control the position of pipes (a metal tube is located on each side of the track to guide the trolley that mills tracks into the ice).…”
Section: Related Workmentioning
confidence: 99%
“…Uma das alternativas para a análise de deformação de estruturas naturais ou artificiais é por meio do monitoramento geodésico, utilizando, por exemplo, sistemas GNSS (Global Navigation Satellite System) (GULAL, 2013;TIWARI et al, 2018;DURDAG et al, 2018); estação-total (URBANČIČ et al, 2020;ZAMINPARDAZ et al, 2020) ou laser scanner terrestre (ANTOVA et al, 2015;HOLST;KUHLMANN, 2016;JAAFAR et al, 2017). Neste contexto, têm-se diversos estudos recentes a nível nacional sobre o tema (MIRANDA; VEIGA, 2016;FERREIRA;CHAVES, 2017;SAMPAIO et al, 2019;GONÇALVES;MEDEIROS et al, 2020;ALVES et al, 2020).…”
Section: Introductionunclassified